Exploring the Rise of Cryptocurrencies in the Financial Market - qizi Shаmsitdinоvа Xоnzоdа Mаrdоnbеk (Journal of Innovation in Education and Social Research, 2024)
The emergence of cryptocurrencies represents a significant shift in the financial landscape, challenging traditional financial systems and introducing a decentralized alternative. This paper explores the rise of cryptocurrencies, examining their origins, market growth, technological foundations, and impacts on global finance. It delves into the regulatory challenges, market volatility, and the potential future role of cryptocurrencies in the financial ecosystem. By reviewing academic literature, market data, and case studies, this study provides a comprehensive analysis of the dynamics driving the cryptocurrency market.